(untitled) (Kronika Bydgoska, 2016)
One of the activities of the State Archive in Bydgoszcz is conservation of its collections in the archives conservation studio. This time, a very precious book of anecdotes and culinary recipes from the collection of the Komierowski family from Komierowo (cat. no. 815/119) was renovated completely. Thanks to the conservation, the book pages were cleaned and strengthened, the block was sewn together again, and the new leather cover was made.